Pengaruh Literasi Keuangan dan Gaya Hidup Hedonisme terhadap Penggunaan Fitur Paylater pada Mahasiswa - Priyadi, Sugeng; Rinawati, Anita (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The development of financial technology, particularly PayLater, has attracted the interest of students and made online transactions increasingly convenient. However, this convenience also carries risks when it comes to financial management, especially for the younger generation who are more consumer-oriented and less knowledgeable about finance. The purpose of this study was to examine how students' financial literacy and hedonistic lifestyle correlate with their use of the PayLater service. This study was conducted using a Systematic Literature Review (SLR) method, reviewing eight relevant journals. The results showed that hedonism and financial expertise negatively impacted PayLater usage, while financial expertise had a positive impact. Students with a good financial understanding tended to use this service more selectively and wisely. Conversely, students who live a hedonistic lifestyle tended to ignore financial risks for the sake of ease of transactions. One way to mitigate the negative effects of a consumer-oriented lifestyle is to learn about finance.